The first three hymns of the Ahunauuaitī Gāthā - Peschl, Benedikt. (Leiden ; Boston)
xix, 552 sayfa
Keywords: “At the center of this book stands a text-critical edition of three chapters of the Gathas, exemplifying the editorial methodology developed by the “Multimedia Yasna“ (MUYA) project and its application to the Old Avestan parts of the Yasna liturgy. Proceeding from this edition, the book explores aspects of the transmission and ritual embedding of the text, and of its late antique exegetical reception in the Middle Persian (Pahlavi) tradition. Drawing also on a contemporary performance of the Yasna that was filmed by MUYA in Mumbai in 2017, the book aims to convey a sense of the Avestan language in its role as a central element of continuity around which the Zoroastrian tradition has evolved from its prehistoric roots up to the modern eralect that split into at least four branches from which in turn the modern NENA dialects emerged“--